Effect of surgical menopause and frontal lobe cognitive function. (4th July 2021) - Orprayoon, N.; Santibenchakul, S.; Hemrungrojn, S.; Phutrakool, P.; Kengsakul, M.; Jaisamrarn, U.; Chaikittisilpa, S.
Abstract: Objective: This study aims to explore the prevalence of decreased frontal lobe function and its associated factors in women with surgical menopause. Methods: This study is a retrospective analysis of a cross-sectional study conducted between October 2013 and July 2014. Data from 164 women with surgical menopause were analyzed. The Montreal Cognitive Assessment Thai version (MoCA-T) test was administered by a psychologist. The MoCA frontal lobe function score was derived from visuospatial/executive, abstraction, attention, and verbal fluency tests. Multivariable logistic regression was used to assess data associated with decreased frontal lobe function. Results: The mean age of participants was 56.3 ± 6.9 years, and the mean time since menopause was 11.3 ± 7.4 years. The prevalence of decreased frontal lobe function score was 73.8%, with an average score of 6.21 ± 1.84. The independent factor associated with a lower MoCA frontal lobe function score was duration of education greater than 6 years. Conclusion: Our study adds information about decreased frontal lobe function in almost three-quarters of women with surgical menopause. Duration of education greater than 6 years was a protective factor. Menopause hormone therapy usage did not seem to increase the detrimental effect on frontal lobe function when initiated in young women with surgical menopause.